El mundo amoroso de Catulo y de la Roma de finales de la República - Blázquez Martínez, José María (Gerión. Revista de Historia Antigua, 2007)
The poet Catullus decribes the love affaires of a Roman high society woman, Lesbia, the Clodia, sister of the deputy of Caesar. Lesbia was a married woman, elegantly and rich. She had many lovers at the same time. Catullus tells us the viciousness of life in Rome at the end of the Roman Republic.